2007
DOI: 10.1038/sj.eye.6702872
|View full text |Cite
|
Sign up to set email alerts
|

Patients' attitudes towards trainee surgeons performing cataract surgery at a teaching hospital

Abstract: Aim To evaluate patients' preferences of surgeon to perform their cataract surgery if given a choice between consultant and trainee. Methods A questionnaire based patient satisfaction survey was conducted in a large University Teaching Hospital in the UK. One hundred and eighty patients undergoing first eye cataract surgery between January and March 2006 were asked a number of set questions on their preferences regarding the surgeon performing the operation. Primary outcome measure was the patient's preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…20 Nearly two third patients at 65% chose the most appropriate explanation of the word assistance in surgery, and a similar 62% respondent felt that the faculty surgeon is the best person to elicit informed consent and disclose and explain resident involvement in their care. This is in contrast with only 26% consent being taken by faculty surgeons as reported in a nationwide survey of surgery trainers by Steeples. 21 Between 52% to 70% respondents had favourable idea of informed consent and role of teaching hospital in resident training similar to the 70% awareness rate reported by Moodie et al and Wisner et al 4,18 We recorded moderate level of acceptance to part performance of surgery at 32% and low level of acceptance to complete performance of surgery at 7% similar to the findings of Nguyen et al reporting only 16% acceptance of resident participation and APORT study recording 35% acceptance for assistance and 11% for performance of surgery, but much lower than the 83% and 49% acceptance of assistance and performance of surgery respectively reported by Wisner et al, 95% acceptance of resident participation reported by Gan et al, 67% acceptance of resident participation reported by Vallance et al and 57% acceptance of resident performance of surgery reported by Moodie et al 4,[16][17][18][19][20] In the Likert psychometric analysis our results were similar to those seen in the APORT study largely because of the similar inclusion criteria but significant differences were seen with reference to the demographic characteristics as the APORT study did not include demographic information and the other reported studies had demographic data which was vastly different from the demographic features of our study population.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…20 Nearly two third patients at 65% chose the most appropriate explanation of the word assistance in surgery, and a similar 62% respondent felt that the faculty surgeon is the best person to elicit informed consent and disclose and explain resident involvement in their care. This is in contrast with only 26% consent being taken by faculty surgeons as reported in a nationwide survey of surgery trainers by Steeples. 21 Between 52% to 70% respondents had favourable idea of informed consent and role of teaching hospital in resident training similar to the 70% awareness rate reported by Moodie et al and Wisner et al 4,18 We recorded moderate level of acceptance to part performance of surgery at 32% and low level of acceptance to complete performance of surgery at 7% similar to the findings of Nguyen et al reporting only 16% acceptance of resident participation and APORT study recording 35% acceptance for assistance and 11% for performance of surgery, but much lower than the 83% and 49% acceptance of assistance and performance of surgery respectively reported by Wisner et al, 95% acceptance of resident participation reported by Gan et al, 67% acceptance of resident participation reported by Vallance et al and 57% acceptance of resident performance of surgery reported by Moodie et al 4,[16][17][18][19][20] In the Likert psychometric analysis our results were similar to those seen in the APORT study largely because of the similar inclusion criteria but significant differences were seen with reference to the demographic characteristics as the APORT study did not include demographic information and the other reported studies had demographic data which was vastly different from the demographic features of our study population.…”
Section: Discussionsupporting
confidence: 61%
“…3 In Cataract surgery there is no suitable surrogate training model that absolutely simulates the live surgery scenario. 4 Informed consent has become a legal requirement before elective surgical procedures. 5 Patients want information about cataract, treatment options, and chances of improvement in vision, risks of deferring the surgery and complications that may occur pre and post operatively.…”
Section: Introductionmentioning
confidence: 99%
“…Further factors that influence training include patients' expectation that their procedure will be performed by a consultant rather than a trainee. 10 Waiting list targets have forced a greater number of cases onto each operating list, creating a pressured environment that cannot accommodate surgical trainees who are likely to operate more slowly. The utilization of Independent Sector Treatment Centers, which tend to select low-risk surgical patients, has not only reduced the number of cases available for training, but also led to a distillation of surgical complexity in National Health Service units.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in relation to cataract surgery, several studies have assessed patient attitudes regarding the participation of trainee surgeons. The current limited literature highlights that patients typically understand the need for surgical training, and a large majority will consent to trainee participation in cataract surgery when this is explicitly discussed . Previous studies highlight that 67% to 70% of patients have positive responses to trainee surgeons performing their operation as part of their training …”
mentioning
confidence: 99%
“…The current limited literature highlights that patients typically understand the need for surgical training, and a large majority will consent to trainee participation in cataract surgery when this is explicitly discussed. [20][21][22] Previous studies highlight that 67% to 70% of patients have positive responses to trainee surgeons performing their operation as part of their training. 8,17,22 Wisner et al 21 used an anonymous survey to study patient attitudes towards resident involvement in their cataract surgery in an academic ophthalmology practice in central Pennsylvania.…”
mentioning
confidence: 99%